2015
DOI: 10.1080/19425120.2015.1040567
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Dependence of Spawning Frequency on Size and Age in Gulf of Mexico Red Snapper

Abstract: In 2011, a large multivessel survey was conducted to provide nearly synoptic sampling of Red Snapper Lutjanus campechanus throughout their reproductive season in the U.S. Gulf of Mexico. A total of 2,487 Red Snapper were caught with a female : male ratio that was approximately 1:1. The ovaries of 1,002 females were histologically examined. Females (n = 391) were found with spawning markers (postovulatory follicles and hydrated oocytes) throughout the study area, but primarily in outer shelf waters. Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 24 publications
4
30
3
Order By: Relevance
“…This reinforces the hypothesis that Red Snapper in the western Gulf may have more varied reproductive potential than fish in the northern Gulf (Lyczkowski‐Shultz and Hanisko ; Porch et al. ).…”
Section: Discussionsupporting
confidence: 86%
“…This reinforces the hypothesis that Red Snapper in the western Gulf may have more varied reproductive potential than fish in the northern Gulf (Lyczkowski‐Shultz and Hanisko ; Porch et al. ).…”
Section: Discussionsupporting
confidence: 86%
“…A potential regional difference in SF detected during the recovery period indicated eastern red snapper spawned slightly more often than conspecifics in the west. While this result contradicts reports that spawning frequency for red snapper is greater in the western Gulf due to the existence of larger fish in that region [20], and our findings corroborate those of Porch et al [20], who found no regional difference in spawning frequency east or west of the Mississippi was found once age or size was considered.…”
Section: Discussionsupporting
confidence: 74%
“…To account for variability in SF estimates caused by the time of day when fish were caught [45] or other factors including accelerated degradation of POFs at warm water temperatures [72], we chose to rely on SF estimates determined using the TC method in this study; this is likely the most accurate method for determining SF because it is inclusive to both day-0 and day-1 fish [34, 48], each of which are known histological spawning indicators [20]. A temporal trend toward less frequent spawning in recent years was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inference is supported by a recent survey of recreational anglers in Texas, which suggested that over 70% of the anglers used artificial reefs, with nearly 40% of these anglers targeting standing platforms (Schuett et al 2015). Moreover, in a GOM-wide study, Porch et al (2015) observed the highest Red Snapper spawning frequencies at natural habitats in our region, further highlighting the potential benefits of the RTR artificial reefs and the diversion of fishing pressure away from natural habitats. Although more detailed study of fishing effort among habitat types is needed, these findings certainly reveal several management implications for RTR habitats versus natural banks.…”
supporting
confidence: 61%